The relationship between DSGE and VAR models - Raffaella Giacomini (Centre for Microdata Methods and Practice (cemmap), 2013)
This chapter reviews the literature on the econometric relationship between DSGE and VAR models from the point of view of estimation and model validation. The mapping between DSGE and VAR models is broken down into three stages: 1) from DSGE to state-space model; 2) from state-space model to VAR; 3) from VAR to finite order VAR. The focus is on discussing what can go wrong at each step of this mapping and on critically highlighting the hidden assumptions. I also point out some open research questions and interesting new research directions in the literature on the econometrics of DSGE models. These include, in no particular order: understanding the effects of log-linearisation on estimation and identification; dealing with multiplicity of equilibria; estimating nonlinear DSGE models; incorporating into DSGE models information from atheoretical models and from survey data; adopting flexible modelling approaches that combine the theoretical rigor of DSGE models and the econometric model's ability to fit the data.
Keywords: 330